2017
DOI: 10.1038/s41467-017-00924-7
|View full text |Cite|
|
Sign up to set email alerts
|

Myoblasts and macrophages are required for therapeutic morpholino antisense oligonucleotide delivery to dystrophic muscle

Abstract: Exon skipping is a promising therapeutic strategy for Duchenne muscular dystrophy (DMD), employing morpholino antisense oligonucleotides (PMO-AO) to exclude disruptive exons from the mutant DMD transcript and elicit production of truncated dystrophin protein. Clinical trials for PMO show variable and sporadic dystrophin rescue. Here, we show that robust PMO uptake and efficient production of dystrophin following PMO administration coincide with areas of myofiber regeneration and inflammation. PMO localization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 56 publications
4
53
0
1
Order By: Relevance
“…DMD patients exhibit chronic inflammation of the heart and skeletal muscle in the form of fibrosis, necrosis, and functional deficiencies. In mdx mice there is an upregulation of Cx43 in the affected muscles, possibly to compensate for increased injury, satellite cell exhaustion and increased myotube regeneration of the muscle [39][40][41][42][43] . Similar to the heart, Cx43 is required for myoblast differentiation in vitro [44][45][46] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DMD patients exhibit chronic inflammation of the heart and skeletal muscle in the form of fibrosis, necrosis, and functional deficiencies. In mdx mice there is an upregulation of Cx43 in the affected muscles, possibly to compensate for increased injury, satellite cell exhaustion and increased myotube regeneration of the muscle [39][40][41][42][43] . Similar to the heart, Cx43 is required for myoblast differentiation in vitro [44][45][46] .…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages have recently been shown to be essential for uptake and slow release of antisense oligonucleotides via Cx43 54,56,57 . The role as a reservoir is necessary for therapeutic administration of partially-functional dystrophin to skeletal fibers and muscle stem cell regeneration for DMD patients 39,43 . Cx43 is not enriched in mdx cardiac macrophages compared to the adjacent cardiomyocytes, reserving a larger role for Cx43 in the cardiomyocytes and skeletal-specific macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…BrdU labeling. BrdU (Sigma-Aldrich, B9285) was administered ad libitum in sterile drinking water at a concentration of 0.8 mg/mL and kept protected from light during administration (50). BrdU was administered from 25 to 28 days (3 days), 25 to 31 days (6 days), and 25 to 34 days (9 days); all animals were euthanized at 38 days of age.…”
Section: Methodsmentioning
confidence: 99%
“… 9 Indeed, we had deciphered the reason for this limited PMO uptake in earlier studies, we had shown that the uptake of the PMOs was limited to the inflammatory foci and active muscle-regenerating regions of the tissue. 25 In the inflammatory foci, PMOs enter into macrophages, activated myoblasts, and fusing myotubes. 25 Of note is also the fact that higher levels of dystrophin could be induced by increasing the PMO doses both in mice 22 , 23 and in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively short half-life of PMOs in plasma (1.62–3.60 hr), together with the recent finding that its uptake is restricted to actively regenerating myofibers, seems to limit its overall efficacy at lower doses, which had been used in the clinical trials so far. 8 , 25 In clinical trials, the level of restored dystrophin by western blot was 0.93% in eteplirsen-treated DMD patients after 180 weeks of administration, compared to healthy individuals (FDA application no. 206488Orig1s000).…”
Section: Introductionmentioning
confidence: 99%